CRISP: Catheterization RISk score for pediatrics: A Report from the Congenital Cardiac Interventional Study Consortium (CCISC). Issue 2 (3rd November 2015) - Nykanen, David G.; Forbes, Thomas J.; Du, Wei; Divekar, Abhay A.; Reeves, Jaxk H.; Hagler, Donald J.; Fagan, Thomas E.; Pedra, Carlos AC; Fleming, Gregory A.; Khan, Danyal M.; Javois, Alexander J.; Gruenstein, Daniel H.; et al.
Abstract : Objectives: We sought to develop a scoring system that predicts the risk of serious adverse events (SAE's) for individual pediatric patients undergoing cardiac catheterization procedures. Background: Systematic assessment of risk of SAE in pediatric catheterization can be challenging in view of a wide variation in procedure and patient complexity as well as rapidly evolving technology. Methods: A 10 component scoring system was originally developed based on expert consensus and review of the existing literature. Data from an international multi‐institutional catheterization registry (CCISC) between 2008 and 2013 were used to validate this scoring system. In addition we used multivariate methods to further refine the original risk score to improve its predictive power of SAE's. Results: Univariate analysis confirmed the strong correlation of each of the 10 components of the original risk score with SAE attributed to a pediatric cardiac catheterization ( P < 0.001 for all variables). Multivariate analysis resulted in a modified risk score (CRISP) that corresponds to an increase in value of area under a receiver operating characteristic curve (AUC) from 0.715 to 0.741. Conclusion: The CRISP score predicts risk of occurrence of an SAE for individual patients undergoing pediatric cardiac catheterization procedures. © 2015 Wiley Periodicals, Inc.